2023
DOI: 10.1186/s13102-022-00606-y
|View full text |Cite
|
Sign up to set email alerts
|

Knee pain in young sports players aged 6–15 years: a cross-sectional study in Japan

Abstract: Background Knee is the most commonly injured part of the body in young athletes. Knee pain in several studies have been seen to be more prevalent in active adolescents compared to inactive, although common in both groups. Nevertheless, few studies with large sample size have been published reporting the difference of the prevalence of knee pain for each sport among young sports players. This study investigated the point prevalence of knee pain among young sports players aged 6–15 years old acco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…The prevalence of GRNP in the 7 th to 9 th grades was approximately two-fold higher than that in the 3 rd to 6 th grades (11.2%, as shown by Sasaki et al, 2023), which could prove our first hypothesis. Another study (Iwatsu et al, 2023) also investigated the point prevalence of knee pain among young Japanese players (7,234 participants from several sports) aged 6-15 years and showed that 13-year-old athletes had the highest rate of knee pain at 19.1%, which is similar to the present results. In an epidemiological study conducted in a Middle Eastern country (Qatar), the prevalence and occurrence rates of apophyseal knee injuries in young elite footballers aged 9-18 years were a median of 33.2% and 13.1 years old, respectively (Materne et al, 2022).…”
Section: Sasaki and Naganosupporting
confidence: 88%
“…The prevalence of GRNP in the 7 th to 9 th grades was approximately two-fold higher than that in the 3 rd to 6 th grades (11.2%, as shown by Sasaki et al, 2023), which could prove our first hypothesis. Another study (Iwatsu et al, 2023) also investigated the point prevalence of knee pain among young Japanese players (7,234 participants from several sports) aged 6-15 years and showed that 13-year-old athletes had the highest rate of knee pain at 19.1%, which is similar to the present results. In an epidemiological study conducted in a Middle Eastern country (Qatar), the prevalence and occurrence rates of apophyseal knee injuries in young elite footballers aged 9-18 years were a median of 33.2% and 13.1 years old, respectively (Materne et al, 2022).…”
Section: Sasaki and Naganosupporting
confidence: 88%
“…Despite their physical benefits, knee injuries are common, particularly in contact and pivoting sports, such as touch football, netball, soccer, rugby union, rugby league, and Australian football. Australia has one of the highest numbers of ACL reconstruction surgeries [ 9 , 10 ]. Most young athletes with knee injuries can resume, to some extent, a level of sports activity through non-pharmacological treatment, such as rest from aggravating activities, icing, and medications if required [ 11 ].…”
Section: Discussionmentioning
confidence: 99%